The varied influence of ocular Demodex infestation on dry eye disease and meibomian gland dysfunction across different age groups - Lee, Won Jun; Kim, Minjeong; Lee, Seung Hyeun; Chun, Yeoun Sook; Kim, Kyoung Woo (Scientific reports, 2023)
This study aimed to investigate the impact of ocular demodicosis on dry eye disease (DED) and meibomian gland dysfunction (MGD) across different age populations: young (20 to < 40), middle-aged (40 to < 60), and elderly (≥ 60), based on the retrospective medical chart review. In each age subgroup, Demodex infestation and its count were correlated with clinical parameters of DED and MGD. Among the total of 351 subjects, 52.7% had ocular demodicosis, with a mean of 2.31 ± 1.39 mites per four eyelashes (0.58 per lash) in a unilateral eye. In the age subgroup 1 (age < 40; N = 44), subjects with Demodex had significantly higher meibum quality grades. In subgroup 2 (40 ≤ age < 60; N = 122), subjects with Demodex had higher ocular surface disease index scores and higher MG expressibility grades. However, in subgroup 3 (age ≥ 60; N = 185), demographics and all parameters did not differ according to Demodex infestation. Moreover, the number of mites did not correlate with MGD severity in any of the subgroups. In conclusion, age may act as a significant confounding factor in the relationship between ocular Demodex infestation and clinical features of DED and MGD, despite older patients aged 60 years and above being at a higher risk of Demodex infestation and experiencing more severe MGD.